RELATIONS OF TWO AUTHORITARIAN REGIMES: SPAIN AND CHILE DURING THE GOVERNMENTS OF PRIMO DE RIVERA AND IBÁÑEZ DEL CAMPO. - Carrellán Ruiz, Juan Luis (Revista de Historia Social y de las Mentalidades, 2024)
This work wants to emphasize the importance  of the diplomatic and economic relations, which  took place during Primo de Rivera and Ibáñez  del Campo mandates, between Spain and Chile.  For that purpose, there has been analyzed the  diplomatic existing documentation in different  Spanish and Chilean Archives. It also reflects  the opinions written on the Spanish press about  the politics designed by Colonel Carlos Ibanez. These relations were based on the ideological  sympathy of both regimes which propitiated  very intense connections in different areas,  such the political and diplomatic areas with  the arbitration agreement signature and the  elevation to the maximum level of both  legations, those of military character with the  Chilean officials training in Spanish training  centres, and those of commercial sign with two  agreements, the reduction of duties and the  internment of saltpetre in Spanish territory
Keywords: Dictatorship; Spain; Primo de Rivera; Chile; Ibáñez del Campo